2010
DOI: 10.1177/0883073810377014
|View full text |Cite|
|
Sign up to set email alerts
|

Expanding Phenotype and Clinical Analysis of Tyrosine Hydroxylase Deficiency

Abstract: This study included 12 Chinese patients with a wide spectrum of phenotypes of tyrosine hydroxylase deficiency. Seven females and 5 males, aged 2.2 to 41 years, had phenotypes ranging from severe type with onset at infancy to mild type with onset after 3 years of age. Patients with the severe type had encephalopathy with poor treatment response or infantile parkinsonism with motor delay. Patients with the less common mild type had dopa-responsive dystonia or a newly recognized predominant symptom of myopathy. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 17 publications
1
38
0
1
Order By: Relevance
“…THD is a very rare genetic disease, with about 70 patients reported worldwide [7,16,51], thus making it an ultra-orphan disease [52]. Research on drug development for these uncommon disorders is rather limited both in academia and in the pharmaceutical industry.…”
Section: Discussionmentioning
confidence: 99%
“…THD is a very rare genetic disease, with about 70 patients reported worldwide [7,16,51], thus making it an ultra-orphan disease [52]. Research on drug development for these uncommon disorders is rather limited both in academia and in the pharmaceutical industry.…”
Section: Discussionmentioning
confidence: 99%
“…It has been already described that the phenotypes and treatment outcomes are related to the lowest HVA levels and a HVA/5-HIAA ratio of less than 1 in the CSF [7,9,10]. Clinical features compatible with dopa-responsive dystonia were the most salient features of the two other patients with A phenotype (9 and 10).…”
Section: Discussionmentioning
confidence: 82%
“…This enzymatic conversion is a rate-limiting step in the biosynthesis of catecholamines. Around sixty patients with TH deficiency have been reported worldwide [1][2][3][4][5][6][7][8][9][10][11]. TH deficiency causes a neurological disease with predominant extrapyramidal signs and a variable response to L-DOPA.…”
Section: Introductionmentioning
confidence: 99%
“…Many different features of THD (hypokinesia, bradykinesia, rigidity, dystonia, tremor, chorea, ptosis, oculogyric crises and hyper salivation, among others) are caused by cerebral dopamine and nor epinephrine deficiency [1,4]. Based on the presenting neurological features, THD usually be divided in two phenotypes: an infantile onset, progressive, hypo kinetic-rigid syndrome with dystonia (type A), and a complex encephalopathy with neonatal onset (type B) [3].…”
Section: Discussionmentioning
confidence: 99%
“…And the trials may be stopped after 6 weeks upon the dose of 450-600 mg/day, if no improvement can be observed [12] . It was reported that selegiline could be added to the treatment to increase the effection some cases [1,4,13].Besides, there is literature mentions that anticholinergics and dopamine agonists may also be effective in the disease [12]. The patient had a complete response to a very low dose of L-dopa within 3 days, so the other medicines were not added.…”
Section: L-dopa Response Is Variable Ranging From Complete Remissionmentioning
confidence: 99%